Method, system, medium and equipment for emerging market subject to participate in power transaction - JIANG HAILONG; CUI JINRUI; LI YONGBO; QIAN HANHAN; WU ZIBO; ZHOU TAO; ZHANG WEISHI; WANG HAICHAO; WANG JIAN; XUAN WEIGE; LIN ZHEMIN; HE CHUAN; et al. (2024)
The invention provides a method, a system, a medium and equipment for an emerging market subject to participate in a power transaction, and the method comprises the steps: 1, defining a reputation value index of a node, which is used for evaluating the historical transaction behavior and the participation degree of each market subject, introducing an incentive mechanism and a punishment mechanism, and optimizing the selection process of a main node; 2, designing a round consensus mechanism, and optimizing a transaction confirmation process through view replacement and proposal priority management; after each round of consensus is completed, view replacement is automatically started, and reward and punishment are carried out according to reputation values of the nodes; and step 3, realizing time synchronization among the nodes through a network time protocol, and monitoring and processing fault nodes in real time through a node health check and fault recovery mechanism. According to the invention, the stabilit